Sistem Pakar Diagnosa Penyakit Henoch-Schonlein Purpura (HSP) Menggunakan Metode ANFIS - Tian Roberto Siburian (BEES: Bulletin of Electrical and Electronics Engineering, 2020)
Technology that is developing in the world is also developed by a technology that is able to deal with the process and way of thinking of humans. Everyone who is specific uses an expert system. In this case, it is a health problem regarding the disease Henoch-Henochein purpura (HSP) Henoch Henochein purpura is an inflammatory disease hymen on the skin, intestinal joints and kidneys that can cause red or purple spaces on the skin. This space is usually found in the lower limbs or bongko, and the number is usually concurrent or large. An expert system can be interpreted as a system that adopts human knowledge into a computer, so that the computer can solve problems as is done by experts, so that the expert system can help experts in solving a problem. The benefits the writer wants to achieve in this study is to help make the expert become younger. To diagnose the disease caused by Henoch Henochein purpura and give contribution to the development of information technology, especially expert systems using the Adptive Neuro Fizzy inference system method.